Glutathione as a Semen Additive to Improve Surti Buffalo (Bubalus bubalis) Bull Semen Cryopreservation - Kumar, Kailash; Gaur, Mitesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study evaluated the effects of glutathione as an additive in Tris fructose egg yolk citrate extender on Surti buffalo bull semen. Extended semen @ 80 million sperm/mL was divided into 4 equal aliquots and glutathione was added at 0.5 mM (T1), 2.0 mM (T2), and 5.0 mM (T3) with one control (T0) group. The percentages of post-thaw sperm progressive motility, live sperm, and HOS responsive sperm were significantly higher (p <0.05), whereas sperm abnormalities were significantly lower (p <0.05) in treatment T1, T2 and T3 compared to T0 control. The treatment T2 (2.0 mM glutathione) had the highest post-thaw sperm progressive motility, live sperm, HOS response sperm percentage and reduced sperm abnormalities compared to other three groups. It was concluded that glutathione at 2.0 mM concentration significantly (p <0.05) improved post-thaw semen quality of buffalo bulls in comparison to control and glutathione concentrations of 0.5 mM and 5.0 mM in Tris extender.